New insights into the benthic macrofauna composition and structure in a southern-west Mediterranean coastal lagoon after restoration actions: Spatial and Seasonal patterns - El Kamcha, Reda; Boutoumit, Soilam; Bououarour, Oussama; Pouzet, Pierre; Maanan, Mohamed; Benhoussa, Abdelaziz; Bazairi, Hocein (Regional studies in marine science, 2023)
The Marchica lagoon (Morocco, Alboran Sea), one of the largest lagoons in the Mediterranean, was subject to various restoration actions in 2011 aiming at enhancing its biodiversity and ecosystem services. Here, benthic macrofauna was investigated (28 stations sampled seasonally in 2015) to assess the functioning on the lagoon after these restorations actions. The ultimate aim was to investigate the spatial and seasonal variation of the benthic macrofauna, the environmental drivers, and the potential effects of the recent bioinvasions. Overall, 131 taxa were identified among which two non-indigenous species (NIS) were recorded: Caprella scaura and Paracerceis sculpta. Multivariate analysis of abundances (cluster analysis and non-metric multi-dimensional scaling) allowed the identification of three main groups of stations totalizing seven macrofaunal assemblages. The species which are dominant and/or discriminate each assemblage are Cymodoce truncata, Elasmopus rapax, Ericthonius brasiliensis, Gammarus insensibilis, Heteromastus sp., Aonides oxycephala, Nereis sp., Loripes orbiculatus, P. sculpta and C. scaura. The macrofaunal assemblage composition are subject to seasonal changes, supported by significant differences in several univariate measures, including total number of individuals, number of taxa, and Shannon–Wiener’s diversity index. Furthermore, the Marchica lagoon showed high values of macrofaunal species richness further supporting the idea that the restoration measures had positive consequences. The distribution of the macrobenthic fauna in the study area was affected by a complex of various factors, with depth, temperature, salinity, sediment characteristics and vegetation biomass being the most important predictor variables. Macrofaunal assemblages significantly correlated with environmental variables; and exhibited a “High” to “Good” status in terms of the impact of alien species according to the Alien Biotic Index. However, the high abundance of NIS detected suggests caution about their impact and further spread.